Evaluation of independent learning module in learning differentiation of history at senior high school level using the CIPP model - Martaliza, Martaliza; Ofianto, Ofianto; Zakaria, Nurhijrah Binti (Program Pascasarjana Universitas Negeri Yogyakarta, 2025)
This study aims to evaluate the independent learning module in differentiated learning in history subject by using CIPP (Context, Input, Process, Product) evaluation model in SMAN 3, SMAN 7, and SMAN 15 Padang. The method used was descriptive-qualitative with an evaluation approach to assess the implementation of curriculum and educational programs. The research was conducted in three stages: pre-research, implementation, and report writing. Data were collected through observation, interviews with history teachers and driving teachers, and documentation, then analyzed using data reduction, data presentation, and conclusion drawing techniques.The results show that differentiated learning aims to meet students' learning needs through specially designed modules. In the context aspect, the school has supported this learning by improving teachers' competence through training and managing the learning environment. From the input aspect, the material in the module is in accordance with Merdeka Curriculum, and resources such as driving teachers and learning media are available, although the learning guide still needs to be refined. In the process aspect, the implementation of differentiated learning is in accordance with planning, using various methods and media that increase student participation, although some teachers experience obstacles in time allocation and student understanding. Product evaluation shows that this learning is effective in improving students' learning outcomes and participation and supporting their learning independence.